6x(2x-5)=6(x-4)+9

Simple and best practice solution for 6x(2x-5)=6(x-4)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x(2x-5)=6(x-4)+9 equation:



6x(2x-5)=6(x-4)+9
We move all terms to the left:
6x(2x-5)-(6(x-4)+9)=0
We multiply parentheses
12x^2-30x-(6(x-4)+9)=0
We calculate terms in parentheses: -(6(x-4)+9), so:
6(x-4)+9
We multiply parentheses
6x-24+9
We add all the numbers together, and all the variables
6x-15
Back to the equation:
-(6x-15)
We get rid of parentheses
12x^2-30x-6x+15=0
We add all the numbers together, and all the variables
12x^2-36x+15=0
a = 12; b = -36; c = +15;
Δ = b2-4ac
Δ = -362-4·12·15
Δ = 576
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{576}=24$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-36)-24}{2*12}=\frac{12}{24} =1/2 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-36)+24}{2*12}=\frac{60}{24} =2+1/2 $

See similar equations:

| −3x+7=1 | | v/6-1.5=-20.7 | | 9-(x-5)=X+10 | | -2(3-4x)=16 | | 12x−7=17 | | v/6-1.5=20.7 | | 3*x+10=30 | | 24x+24-44x+44=-100 | | 7w-9=11-3w | | 5(2x+6)=4(x+12 | | 24x-24-44x-44=-100 | | (5x-11)+121+(3x-2)=180* | | -6b+5=-1 | | (5x-11)+121+(3x-2)=180 | | (9x+8)+(10x)+(8x+10)=180* | | 3x-4-2×=16 | | 6x+10+2=2x+20 | | -5*k=12 | | -5×k=12 | | 1-0.2x-0.48x^2=0 | | 4y=−24 | | 1.15/0.85=m/1.19 | | 108-w=260 | | 25x+17x=336 | | 3(-n-4)=30 | | 5x+9x+24=150 | | 1.15/0.85=m | | 6x-0=108 | | 4x+10+140=360 | | 7x-3+3x-4=180 | | Y=0.004x+7.45 | | 7x-18=16x-2 |

Equations solver categories